Membongkar Kekerasan di Balik Metafor 'Nak Jawa': Unveiling the Violence Behind the 'Nak Jawa' Metaphor - Siti Raudlotul Jannah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2010)
The term 'Nak Jawa' is connected not only to emigrants from Java but also to those from Sumatera, Kalimantan, Sulawesi, Lombok, and other Muslim emigrants. Typically, the term 'Nak Jawa' is used to differentiate between emigrants and the native Hindu population of Bali. The metaphor of 'Nak Jawa' carries a meaning that goes far beyond just those two words. By being labeled as 'Nak Jawa,' Javanese workers or those categorized as such are positioned as individuals seeking a livelihood in Bali (emigrants), and thus, they are expected to be more respectful, submissive, obedient, and non-arrogant toward the landowners (Nak Bali). As a result, 'Nak Jawa' should not dare to oppose 'Nak Bali,' who are the rightful owners of the territory. This research attempts to reveal the violence embedded in the 'Nak Jawa' metaphor in Bali. Istilah 'Nak Jawa' tidak hanya merujuk pada perantau dari Jawa, tetapi juga pada perantau dari Sumatera, Kalimantan, Sulawesi, Lombok, dan perantau Muslim lainnya. Biasanya, sebutan 'Nak Jawa' digunakan sebagai pembeda antara pendatang dan penduduk asli Bali yang beragama Hindu. Metafor 'Nak Jawa' memiliki makna yang jauh lebih dalam daripada sekadar dua kata tersebut. Dengan disebut sebagai 'Nak Jawa', pekerja beretnis Jawa atau yang dikategorikan ke dalamnya akan diposisikan sebagai pencari nafkah di Bali (perantau), sehingga mereka diharapkan lebih hormat, mengalah, taat, dan tidak arogan terhadap pemilik tanah (Nak Bali). Karena itu, 'Nak Jawa' dianggap tidak boleh kurang ajar atau berani melawan 'Nak Bali' yang merupakan pemilik wilayah. Penelitian ini berupaya mengungkap kekerasan di balik metafor 'Nak Jawa' di Bali.